Neuropsychological Functioning and Health-Related Quality of Life. Issue 1 (January 2015) - Sorensen, Lisa G.; Neighbors, Katie; Zhang, Song; Limbers, Christine A.; Varni, James W.; Ng, Vicky L.; Squires, Robert H.; Alonso, Estella M.
ABSTRACT Objectives: Pediatric acute liver failure (PALF) is a rare but serious event, with poorly understood functional outcomes. The goal was to determine the prevalence of reduced neuropsychological functioning and health-related quality of life (HRQOL) following PALF. Methods: This multicenter study examined neuropsychological functioning and HRQOL 1 to 6 (median 3.8) years after PALF. Participants ages 6 to 16 (median 9.9) years were recruited from the PALF registry and administered measures of intelligence, visual spatial/visual motor coordination, attention, executive function, depression, and adaptive skills. HRQOL and fatigue were assessed using the Pediatric Quality of Life Inventory 4.0 Generic Core Scales (PedsQL 4.0) and PedsQL Multidimensional Fatigue Scale. Results: A total of 36 patients participated; 50% were boys and 67% were white. Median age at PALF was 5.6 years. A history of grade 3 or 4 hepatic encephalopathy was reported in 5/36 (14%) participants and 23/36 (64%) received a liver transplant. Visual spatial ability was significantly better than norms (P = 0.009), but motor coordination was worse (P = 0.04). Teachers (P = 0.04 to P < 0.0001) and parents (P = 0.005) reported more executive deficits versus norms, and participants had worse attention (P = 0.02). Participants did not differ significantly from norms on IQ, depression, or adaptive functioning. All of the child self-report PedsQL Generic Core and fatigue scales were significantly lower than a matched healthy sample (P = 0.001 to P < 0.0001) and parent proxy report was lower on the fatigue scales (P = 0.001 to P < 0.0001). Conclusions: Long-term PALF survivors demonstrate average IQ and visual spatial ability, but greater than expected impairments in motor skills, attention, executive function, HRQOL, and fatigue.